PERENCANAAN KEPALA MADRASAH DALAM MENGEMBANGKAN SUMBER DAYA PENDIDIK - Nurul Ade Mantika; Yudin Citriadin; Bahtiar (Universitas Tidar, 2023)
The madrasa head is a very important and strategic factor in the framework of improving the quality and progress of the madrasa he leads. It can be seen that to achieve the quality and progress of the madrasa, the head of the madrasa is a role model for the entire madrasa community who have the ability to plan better and more advanced madrasas. This study uses a qualitative approach with a case study type of research. This research is located at the Baiturrahman Dompu Islamic Elementary School. Data analysis uses display data, data condensation and conclusion drawing. The results of the study show that the principal has been able to plan and develop educational resources and the planning carried out by the principal has been able to meet the needs of teachers and students both directly and indirectly.